2016
DOI: 10.1002/cpe.4013
|View full text |Cite
|
Sign up to set email alerts
|

Astroturfing detection in social media: a binary n‐gram–based approach

Abstract: Summary Astroturfing is appearing in numerous contexts in social media, with individuals posting product reviews or political commentary under a number of different names, and is of concern because of the intended deception. An astroturfer works with the aim of making it seem that a large number of people hold the same opinion, promoting a consensus based on the astroturfer's intentions. It is generally done for commercial or political advantage, often by paid writers or ideologically motivated writers. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The approach consisted of extracting the user's writing style, uses the k-Nearest Neighbors algorithm (k-NN) to evaluate the post content and identify the user, and uses a continuous updating of the user baseline to support existing trends and seasonality issues of the user's posts. The findings reported by the authors in this special issue, as well as those of Peng et al [14]) and Peng et al [15]) demonstrated the potential to identify users based on the textual contents of their postings on social media.…”
Section: Social Networksupporting
confidence: 59%
“…The approach consisted of extracting the user's writing style, uses the k-Nearest Neighbors algorithm (k-NN) to evaluate the post content and identify the user, and uses a continuous updating of the user baseline to support existing trends and seasonality issues of the user's posts. The findings reported by the authors in this special issue, as well as those of Peng et al [14]) and Peng et al [15]) demonstrated the potential to identify users based on the textual contents of their postings on social media.…”
Section: Social Networksupporting
confidence: 59%
“…Similarly, classification methods such as K-Nearest Neighbors [21], Gradient Boosted Decision Trees [23] and Support Vector Machines [17] have been used for identifying user based on their profiles. In addition, some works follow an information retrieval approach and estimate distance metrics for ranking possible users for a given content [22,33]. In this work, we employ a single-label multi-class model approach, where each class correspond to a specific user, and the content could be assigned exclusively to one user.…”
Section: Related Workmentioning
confidence: 99%
“…The IRA's accounts have been created in such a way that they are portrayed as real American accounts. Masking the sponsor of a message such that it appears to originate, and be supported by, grassroots participants is also known as astroturfing (Peng et al, 2017). Based on a 2018 Pew Report, 53% of the Americans participate in some form of civic or political activities on social media during the year (Anderson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%